Effect of breakfast cereal type on portion size and nutritional implications. Issue 11 (17th August 2021) - Lewis, Isabelle M; Boote, Lucy; Butler, Tom
Abstract: Objective: The present study aimed to assess the effect of different types of breakfast cereal (BC) on portion size and the nutritional implications of potential under or overserving. Design: A cross-sectional analysis was performed using one BC from the seven established BC manufacturing methods (flaking (F), gun puffed (GP), oven puffed (OP), extruded gun puffed (EGP), shredded wholegrain (SW), biscuit formed (BF) and granola). Participants were asked to pour cereal as if they were serving themselves (freepour). Difference between the freepour and recommended serving size (RSS) was calculated (DFR). The Friedman test followed by Dunn's multiple comparison test was used to test for a significant differences between cereal categories. Setting: City of Chester, North West of the UK. Participants: Adults ( n 169; n 110 female, 32 (sd 18) years). Results: Freepour values were greater than RSS for all categories of BC. Median values for denser cereals such as SW, granola and oats were significantly ( P < 0·001) greater than all other categories with granola having the highest median freepour value of 95 g. Median (and range of) DFR weight values for granola were significantly higher than other BC (50·0 g (−24·0 to 267·0 g), P < 0·001). BC with the lowest median DFR were F1 (7·0 g (−20 to 63·0 g)), GP (6·0 g (−26·0 to 69·0 g)), EGP (6·0 g (−26·0 to 56·0 g)), OP (5·0 g (−27·0 to 53·0 g)) and BF (0·0 g (−28·2 to 56·4 g)). Conclusions: The degree of overserving may be related to the type of BC with denser cereals more readily overserved. Encouraging manufacturers to reformulate cereals and improving their nutritional properties may have benefit in reducing excess energy intake.